A Methods engineering study on Gromax Incorporated - Angeles, Wilfred Gabriel (College of Engineering, 2001)
The study aims to provide the group with real-life applications of the tools and concepts in the field of Methods Engineering through a project-based study of a manufacturing company. The study intends to identify the major concerns of the company and recommend alternative actions to address the problems affecting its production operations to enable the company to function more efficiently and effectively and thus increase its productivity. The company under study, GROMAX, Incorporated manufactures animal health and nutritional products for commercial sales as well as for contract growing operations of its parent company, the Vitarich Corporation. Its major product lines are feed premix, water solubles, oral solutions and disinfectants. The group decided to focus on the product line that has the greatest daily production output and hence chose the feed premix product line. The summary of findings from the examination of the single product line in focus was used as an indicator of the company's systems of operations as a whole. The group conducted plant visits and observations to gather information about the company's production operations on feed premix. The group also performed personnel interviews to collect additional information for the problem identification and verifications. The group identified and verified problems in several categories, method, material, machine, environment and man. The group utilized the Streamline Diagnostic chart to identify the problem(s) to be focused on. Inefficient plant layout and uneven job distribution were identified as the major problems of the company. Inefficient layout was chosen because it causes two major problems that affect the production process namely the long travel time/distance and the lack of storage space. Uneven job distribution was chosen because it occurs in every production cycle and accumulates production idle time, thus affecting the production output of the company. The group developed alternative plant layouts and methods to address the two main problems respectively. From the evaluation of the alternatives, interchanging of the production area and the cold room with provision of a door connecting the two proved to be the best layout among the alternatives developed since this would ensure shorter travel distance between the two interacting rooms and would also bring the production area and the storage area finished products closer. The group recommends the implementation of redistribution of work among the four production crew since it contributes a greater increase in profit, from 743,000 to 1,032,000 as compared to the profit of 867,400 generated by the alternative of eliminating the bagger, The group also recommends the implementation of good housekeeping to address the other problems of the company such as lack of storage and also to provide a safer and more orderly environment that is conducive to work.